Preventive International Legal Protection Against the Looting of Underwater Cultural Heritage International Legal Protection (Case Study of the Looting of the Merchant Ship Fort Royal 1 in the Mediterranean Sea) - Fridina Tiara Khanza; Elisabeth Septin Puspoayu (NOVUM : JURNAL HUKUM, 2024)
Case of looting of goods in the trading ship Fort Royal 1 in the Mediterranean Sea located on the continental shelf is a violation of international legal protection of Underwater Cultural Heritage. The looting violates provisions of the 2001 UNESCO Convention. Looting can result in the loss of human cultural heritage in the past. The purpose of this study is to identify the protection of underwater cultural heritage according to international law as well as the responsibility of the state due to the looting of Underwater Cultural Heritage. The research method used is normative legal research using legislation approach, case approach, and conceptual approach. The existence of cases of looting of goods in the trading ship Fort Royal 1 in the Mediterranean Sea proves that the lack of strict safeguards and strict rules regarding the protection of Underwater Cultural Heritage. France as a state party is still in the process of investigating the search for looters and looted goods. France as a state party must certainly take responsibility for the looting that occurred, namely by way of restitution and satisfaction.